COMPARATIVE ANALYSIS OF HYPERBOLA IN O‘TKIR HOSHIMOV’S “DUNYONING ISHLARI” AND ITS TRANSLATION “SUCH IS LIFE”. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This study examines the use and translation of hyperbole in the English version of O‘tkir Hoshimov’s “Dunyoning Ishlari”, translated as “Such is Life” by Mark Reese and Abdulloh Ro‘ziyev. Hyperbole serves as a key stylistic device in Uzbek narrative prose, particularly in emotionally charged and humorous contexts. Using a qualitative textual analysis approach, the study compares selected examples from the source and target texts to evaluate semantic fidelity, stylistic equivalence, and cultural resonance. Findings show that the translators primarily use dynamic equivalence to preserve emotional intensity and reader engagement. While most hyperboles are successfully maintained, some culturally bound exaggerations undergo softening due to structural and idiomatic constraints in English. The study highlights the importance of effect-based strategies in literary translation and suggests that hyperbole can be effectively conveyed across linguistic and cultural boundaries when translation prioritizes communicative impact.